Magnetic Resonance Imaging to Visualize Stroke and Characterize Stroke Recovery: A Review - MacIntosh, Bradley J.; Graham, Simon J. (Frontiers in Neurology, 2013)
The global burden of stroke continues to grow. Although stroke prevention strategies (eg. medications, diet and exercise) can contribute to risk reduction, options for acute interventions (eg. thrombolytic therapy for ischemic stroke) are limited to the minority of patients. The remaining patients are often left with profound neurological disabilities that substantially impact quality of life, economic productivity, and increase caregiver burden. In the last decade, however, the future outlook for such patients has been tempered by movement away from the view that the brain is incapable of reorganizing after injury. Many now view brain recovery after stroke as an area of scientific research with large potential for therapeutic advances, far into the future [1]. As a probe of brain anatomy, function and physiology, magnetic resonance imaging is a noninvasive and highly versatile modality that promises to play a particularly important role in such research, towards improving stroke rehabilitation methods and stroke recovery.